Experimental Studies on 3D Printing of Automatically Designed Customized Wrist-Hand Orthoses - Górski, Filip (Materials (Basel), 2020)
The paper presents results of research conducted on a batch of additively manufactured individualized openwork wrist–hand orthoses made of thermoplastics and designed automatically based on 3D-scanned geometry of a given patient. The aim of the work was to establish an automated design process and find a reliable set of parameters for rapid and affordable manufacturing of usable orthoses on popular 3D printers, with little or no supervision of the process. The paper presents motivations, methodology of automated design, plan of manufacturing and testing, the obtained results in terms of process stability, fit and assessment by patient and strength of the obtained orthoses. Almost 100 manufacturing processes of ready-to-use orthosis parts were carried out in a controlled environment and their results were analyzed thoroughly. The results are promising, as most of the obtained products fulfil the strength criteria, although not all of them meet the economic criteria. As a result, a recommended set of process parameters was determined. These parameters were included in a prototype of the automated design and in a production system developed by the authors.